PENGARUH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN TERHADAP PERILAKU DISIPLIN SISWA KELAS VIII DI SMP N 1 PANGKALAN LESUNG KABUPATEN PELALAWAN - Thoifah '; Gimin '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the lack of discipline behavior,so the writer decidedes that the litle of this study " the effect citizenship education learning toward discipline behavior VIII of junior high school 1 (SMPN 1) of Pangkalan Lesung Pelalawan District”. The problem of this research is how the effect citizenship education learning toward discipline behavior VIII of junior high school 1 (SMPN 1) of Pangkalan Lesung Pelalawan District. This study aims to find out the effect citizenship education learning toward discipline behavior VIII of junior high school 1 (SMPN 1) of Pangkalan Lesung Pelalawan District. This study uses a sample Non-Probability sampling is saturated. The sample consists of all of VIII grade student in Junior High School 1 (SMPN 1) Pangkalan Lesung Pelalawan District, they are 82 students. Data collection instruments consists of 33 questions, 16 questions for the X variables and 17 questions for the Y variable. Data were analyzed using simple linear regression. Based on data analysis there are some the effect citizenship education learning toward discipline behavior VIII of junior high school 1 (SMPN 1) of Pangkalan Lesung Pelalawan District. This is proved by a series of simple linear regression test between the variables X and Y, obtained Fhitung 15.96 and Ftabel 3.96 value obtained from the study of the distribution of F table with N = 82, At significant level of 5%, thus Fhitung > Ftabel, or 15.96> 3.96. Thus, the hypothesis in this study is accepted that there is a significant the effect citizenship education learning toward discipline behavior VIII of junior high school 1 (SMPN 1) of Pangkalan Lesung Pelalawan District.Keywords: learning Citizenship Education. Discipline behavior